Economic Empowerment of Farmers through Adoption of Vegetable Cultivation Technology in Hadoti Region of Rajasthan (Indian Journal of Extension Education, 2017)
The study was undertaken in Jhalawar district of Rajasthan. Data were solicited from randomly selected 60 beneficiary and 60 non-beneficiary vegetable growers of Krishi Vigyan Kenddra (KVK) Jhalawar district, Rajasthan, India. The important interventions extended by KVK Jhalawar among farmers were vegetable varieties, time of sowing, plant protection measures, and fertilizer application. Findings of the study revealed that technological interventions extended by KVK have significantly empowered the vegetable growers technologically and economically. Higher extent of adoption of timely sowing, balanced fertilizer use and plant protection measures by the beneficiary respondents resulted in less cost of cultivation (Rs. 8,350/-) and higher net income (Rs.1,04,200/-) from vegetable cultivation than the non-beneficiary respondents.